Level of Antibiotic Resistance in Vibrio parahaemolyticus Bacteria Isolated from Shrimp: Observation of Shrimp Ponds in South Sulawesi Province - Hamzah, Hamzah; Mundayana, Yuani; Srinawati, Srinawati; Afandi, Alfa Astiana; Batubara, Habson; Lideman, Lideman; Sahabuddin, Sahabuddin; Akmal, Akmal; Syaichudin, Mochammad Astiana; Faridah, Siti; Sudrajat, Imam; Gafur, Abdul (Perhimpunan Intelektual Muslim Indonesia, 2024)
The presence of Vibrio parahaemolyticus in shrimp ponds needs to be a concern because it is an opportunistic pathogen. Although V. parahaemolyticus can aid shrimp digestion, an increase in its population can negatively impact shrimp conditions. Currently, there are concerns about antibiotic-resistant V. parahaemolyticus due to the use of antibiotics in aquaculture activities. Antibiotic resistance is not only caused by unwise use of antibiotics but can also occur due to mutations between bacteria in the aquatic environment. Therefore, it is important to determine the presence or absence of antibiotic-resistant V. parahaemolyticus from shrimp farming activities in ponds. Early detection will be crucial for policymakers regarding the use of antibiotics in pond shrimp farming and provide information for shrimp farmers about the effectiveness of the antibiotic use they have taken. This study aims to observe antibiotic resistance in V. parahaemolyticus bacteria obtained from ponds in South Sulawesi Province. Based on observations made in four districts, the results showed that no V. parahaemolyticus was found to be resistant to the three types of antibiotics tested. It can be concluded that shrimp from ponds in South Sulawesi Province are still free from antibiotic-resistant V. parahaemolyticus. Nevertheless, continuous vigilance and monitoring of this problem is still needed to maintain the sustainability of the shrimp farming industry and food safety